The Aim Justifies the Means—Differences Among Musical and Nonmusical Means of Relaxation or Activation Induction in Daily Life - Kappert, Mattes B.; Wuttke-Linnemann, Alexandra; Schlotz, Wolff; Nater, Urs M. (Frontiers in Human Neuroscience, 2019)
Music is an effective means of stress-reduction. However, to date there has been no systematic comparison between musical and language-based means of stress reduction in an ambulatory setting. Furthermore, although the aim for listening to music appears to play a role in its effect, this has not yet been investigated thoroughly. We compared musical means, language-based means like guided relaxation or self-enhancement exercises, and a combination of both with respect to their potential to reduce perceived stress. Furthermore, we investigated whether the aim one wants to achieve by listening to these means had an impact on their effect. We tested 64 participants (age: M = 40.09 yrs.; 18 female) for 3 to 10 days during their everyday life using an app containing three means: musical means language-based means, and a combination of both. For the music and the combination conditions participants were asked to select an aim: relaxation or activation. We measured perceived stress, relaxation, activation, and electrical skin resistance (ESR) as a marker of SNS activity before and after using the app. Participants were instructed to use the app as often as desired. Overall, perceived stress was reduced after using the app, while perceived relaxation and activation were increased. There were no differences between the three means regarding the effect on perceived stress and relaxation, but music led to a greater increase in ESR and perceived activation compared to the other means. There was a decrease in ESR only for music. Moreover, perceived stress was reduced and perceived relaxation was increased to greater extent if the aim ‘relaxation’ had been selected. Perceived activation, however, showed a larger increase if the aim had been ‘activation’, which was even more marked in the case of music listening. Our results indicate that all three means reduced perceived stress and promoted feelings of relaxation and activation. For enhancing feelings of activation music seems to be more effective than the other means, which was reflected in increased SNS activity as well. Furthermore, the choice of an aim plays an important role for the reduction of stress, and promotion of relaxation and activation.